Evaluating the Effectiveness and Safety of a Shortened Rifapentine-Moxifloxacin Regimen in Treating Drug-Sensitive Pulmonary Tuberculosis: A Systematic Review - Luthfia Ayu Wicaksana; Endy Amos Todo Hasudungan Sirait (Medicinus, 2026)
Background: Prolonged treatment duration remains a key challenge in managing drug-sensitive pulmonary tuberculosis (DS-TB), contributing to poor adherence and treatment failure. Recent evidence suggests that regimens incorporating rifapentine and moxifloxacin (RPT+MOX) may allow for effective 4-month treatment courses. Methods: We conducted a systematic review and meta-analysis following PRISMA 2020 guidelines to evaluate the effectiveness and safety of shortened RPT+MOX regimens. PubMed, EMBASE, and Scopus were searched up to May 2025. Eligible studies included randomized trials or observational cohorts comparing shortened RPT+MOX regimens with standard 6-month therapies in patients with DS-TB. Outcomes included culture conversion at 8 weeks, relapse or treatment failure, and serious adverse events. Risk of bias was assessed using the ROBINS-I tool. Result: Five studies (three RCTs, two observational) met inclusion criteria. Pooled analysis showed no significant difference in risk for relapse or treatment failure (RR 0.79, 95% CI: 0.37–1.67), culture conversion (RR 1.16, 95% CI: 0.80–1.69), or serious adverse events (RR 0.92, 95% CI: 0.65–1.29) between RPT+MOX and standard regimens. Risk of bias ranged from minimal to moderate. The GRADE assessment supported high certainty of evidence. Conclusions: Shortened RPT+MOX regimens demonstrate comparable effectiveness and safety to standard 6-month treatment for DS-TB, supporting their use in appropriate settings. Further studies are warranted to assess long-term outcomes, real-world adherence, and feasibility across diverse populations.